Chemical Analysis of Air Particulate Matter Trapped by a Porous Material, Synthesized from Silica Fume and Sodium Alginate. (12th March 2019) - Bilo, Fabjola; Zanoletti, Alessandra; Borgese, Laura; Depero, Laura E.; Bontempi, Elza
Abstract : This work shows the ability of a new porous material (SUNSPACE), obtained by industrial by-products, to sequestrate air particulate matter (PM). This activity allows introducing the azure chemistry approach, devoted to better link new remediation strategies and sustainability. In particular, SUNSPACE is synthesized from silica fume and sodium alginate; it can be shaped in a porous solid, and it looks promising for environmental application as nanoparticle sequestration. Studies to evaluate the sequestration capability of SUNSPACE are performed in different environments, with and without anthropogenic sources of PM. Solid SUNSPACE disc samples are used as passive samplers and exposed for one and two months, in vertical and horizontal positions, indoor, and outdoor. Total reflection X-ray fluorescence technique is employed to perform elemental chemical analysis of the entrapped PM. Two sample preparation strategies to evaluate the composition of PM are considered: sample sonication in Milli-Q water and total sample mineralization by microwave acid digestion. These two options are proposed to analyse different PM fractions: in particular, sonication allows removing the coarse PM, entrapped on external material surface pores; on the contrary, digestion can offer information on fine and ultrafine PM, trapped in internal pores. Results confirm the ability of the porous material to sequestrate air PM and the differences in the sample preparation, supported by elemental analysis, and show the difference in the coarse and fine air particulate matter composition. In summary, the new material results as very promising for applications requiring nanoparticle sequestration.